Influência do fogo sobre a condição corporal de Rhipidomys macrurus (Gervais, 1855) (Rodentia: Cricetidae) no Cerrado brasileiro - Pereira, Déborah Carolina Oliveira (2024)
Disturbances may cause several changes in physiological, behavioral and demographic parameters of organisms, which may translate into changes in community structure and ecosystem functioning. Little is known about the effects of fire on physiological parameters, and how these may affect population dynamics and persistence. Considering current climate change and anthropogenic pressures, fire has become more intense and frequent in several Brazilian biomes, including the Cerrado. In this sense, it is urgent to assess the effects of fire on organism's physiology, especially on metrics that reflect nutritional state. We used a longitudinal database (9 years) to test the effects of fire on the body condition of the tree rat Rhipidomys macrurus at the Estação Ecologica do Panga (Uberlandia/MG). The effects of sex and climatic season on body condition were also tested. Overall, we failed to corroborate our hypothesis, as body condition was not affected by repeated fires. Several mechanisms may account for this result: 1) reduced intraspecific competition after repeated fire events, due to abrupt changes in the rodent density, 2) fire acting as a selective agent, leading to increased mortality of individuals with lower body condition and nutritional reserves, and 3) adoption of behavioral strategies that may compensate energy loss and hence help to minimize the negative impacts of fire on body condition. Furthermore, other variables associated with individual fitness may be more affected by fires than body condition. Our results contribute to the theory that body condition may not be a reliable indicator of habitat quality and disturbance, as well as individual and population health.